Nilai Pendidikan Karakter dalam Ekspresi Lingual Angngaru - Wardah Afdaliah; Syekh Adiwijaya Latief; Anin Asnidar (Pusat Riset dan Inovasi Nasional, 2025)
In general, this research aims to describe the character education values contained in Angngaru local culture. The specific objective is to produce a contribution of thought to revitalize character education by referring to local cultural values. This research method is naturalistic research. The data sources in this research are words, phrases, and sentences that contain character education values. The data collection technique is done with documentation, reading, and note-taking techniques. The results of the research and discussion can be concluded that 6 out of 18 character education values were found in Angngaru lingual expressions. These values are (1) The form of religious character education value, (2) The form of discipline character education value, (3) The form of national spirit character education value, (4) The form of love for the country character education, (5) The form of social care character education, (6) The form of responsibility character education. The value of religious character education is a value that displays aspects of religious teachings in life. The value of discipline character education is the act of obeying established rules, norms or principles, both in personal and social life.The character education value of national spirit is a way of thinking and acting that prioritizes the interests of the nation and state above the interests of self and group. The character education value of patriotism is an attitude that shows loyalty and concern for the social, cultural, economic and political conditions of the nation. The value of responsibility is a person's awareness of the obligations that must be carried out and the readiness to accept the consequences of each action.